Employment and fertility in East Germany after unification - James C. Witte; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
Vital statistics clearly indicate that the fertility rate in East Germany dropped sharply after German unification; moreover, it has not yet rebounded but remains stable at a low level. This paper uses data from the German Socio-Economic Panel (GSOEP) to examine births in the former German Democratic Republic in 1992 and 1993. The primary explantory variables include women's employment status in 1991 and 1992, expectations about future unemployment, and the employment status of cohabiting or marital partners. Our hypothesis is that young women who become unemployed are likely to use this occasion to become pregnant. We assume that the preference for children has not changed dramtically among East German women following unification. Support for this assumption is found in data from the GSOEP, which indicates that the value women attach to family life has remained relatively stable. Instead of viewing the decline in fertility as a shift in preferences, it is viewed as a change in opportunity costs. In general, there are long-term opportunity costs associated with an interruption in employment due to the subsequent devaluation of human capital. Specifically, in East Germany the re-entry rates of unemployed people into the labor market are very low. As a result: 1) the opportunity costs of having a child are quite high for employed women since they are likely to experience difficulties reentering the labor force; 2) for women outside the employment system, who are likely to remain there, the opportunity costs are quite low. In examining this question we make use of the household orientation of the GSOEP and also consider the employment status of each woman's partner, married or cohabiting, if the woman shares a household with such a person. Along with these theoretical issues this paper also addresses an interesting theme in the public debate regarding fertility changes in East Germany. Our results run counter to a widely held belief that young women become unemployed because they get pregnant. Instead, our longitudinal analyses suggest that the timing goes in the other direction: women become pregnant after they are unemployed.
Keywords: 330; Fertilität; Frauenarbeitslosigkeit; Weibliche Arbeitskräfte; Familienökonomik; Neue Bundesländer